ENGLISH STUDENTS SELF-ACTUALIZATION AND THEIR ENGLISH ACHIEVEMENT - Sualang, Lely (11th International Scholars Conference, 2016)
This study is intended to find whether there is a relationship between students self-actualization and their English achievement. The 159 students of General English 1, 2, 3, and 4 were the respondents for this study. Convenience and Purposive Sampling Methods were used to collect the data. The findings revealed that English students self-actualization was high, their English achievement was above average, and no significant difference of student self-actualization based on gender, English level, and faculty. However, there were significant differences of English students achievement based on English level and faculty. Finally, there was no significant correlation between English students self-actualization and their English achievement. General English 1, 3, and 4 students are recommended to improve their English achievement by enhancing their creative thinking and hard work.